Arterial Hypertension: Figures to Define it at the Onset 2018 - Alfredo Darío Espinosa Brito (Universidad de las Ciencias Médicas de Cienfuegos, 2018)
Arterial hypertension in a known health problem but still it does not seem to be easy to determine in a feasible and unequivocal, who suffers from hypertension or not, in a community at a given moment. Blood pressure figures, from which it has been considered a patient as hypertensive, have been modified in time according to the knowledge, available evidence and predominating opinions in each moment and place. Guidelines constitute a methodological tool with the purpose of improving the quality of the medical care. And guarantee the patients safety. Controversial aspects are approached related to the new changes on the figures considered for the diagnosis and control of this condition concerning the publication of the last guidelines for the diagnosis and management of arterial hypertension in 2017. The harmonic balance between the updated knowledge, systematized and adjusted from the guidelines, the correct clinical judgment and the professional ethics in caring for the patients, including hypertensive, constitutes the ideal combination for all medical performance.